2014
DOI: 10.4238/2014.april.17.9
|View full text |Cite
|
Sign up to set email alerts
|

Heliconia phenotypic diversity based on qualitative descriptors

Abstract: ABSTRACT. The aim of this study was to characterize Heliconia genotypes phenotypically using 26 qualitative descriptors. The evaluations were conducted in five flowering stems per clump in three replicates of 22 Heliconia genotypes. Data were subjected to multivariate analysis, the Mahalanobis dissimilarity measure was estimated, and the dendrogram was generated using the nearest neighbor method. From the values generated by the dissimilarity matrix and the clusters formed among the Heliconia genotypes studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Guimarães et al [13] registered the presence of wax in pseudostem on H. bihai whilst Costa et al [21] reported a bigger length in the inflorescence. This variation can be highly influenced by the environment since temperature conditions and rainfalls vary from 26˚C to 1, 968 mm [20].…”
Section: Phenotypic Diversitymentioning
confidence: 99%
See 3 more Smart Citations
“…Guimarães et al [13] registered the presence of wax in pseudostem on H. bihai whilst Costa et al [21] reported a bigger length in the inflorescence. This variation can be highly influenced by the environment since temperature conditions and rainfalls vary from 26˚C to 1, 968 mm [20].…”
Section: Phenotypic Diversitymentioning
confidence: 99%
“…Group III (GIII) was integrated by five accessions, which are easily distinguishable for presenting wax in the limb [13], leaf growth in an oblique position, pubescence on inflorescence, undulated rachis, and a helicoidal arrangement in the bracts. Accession C1 was associated to this group due to the short size of the plant, which is probably in response to where the characterization was carried out [20].…”
Section: Phenotypic Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Morphologic descriptors have been frequently employed for the determination of phenotypic diversity and to differentiate some Heliconia cultivars and interspecific hybrids (Berry and Kress, 1991;Loges et al, 2007;Costa et al, 2009;Guimarães et al, 2014). These descriptors are usually multi-categorical and qualitative, related to plant structural features and morphology, or even binary when referring to the absence or presence of a certain characteristic (Guimarães et al, 2014).…”
Section: Introductionmentioning
confidence: 99%